Influence of Nd and Ce doping on the structural, optical and electrical properties of V2O5 thin films - Jassim, I. K. (Iraqi Journal of Physics, 2019)
Nano-structural of vanadium pentoxide (V2O5) thin films weredeposited by chemical spray pyrolysis technique (CSPT). Nd and Cedoped vanadium oxide films were prepared, adding Neodymiumchloride (NdCl3) and ceric sulfate (Ce(SO4)2) of 3% in separatesolution. These precursor solutions were used to deposit un-dopedV2O5 and doped with Nd and Ce films on the p-type Si (111) andglass substrate at 250°C. The structural, optical and electricalproperties were investigated. The X-ray diffraction study revealed apolycrystalline nature of the orthorhombic structure with thepreferred orientation of (010) with nano-grains. Atomic forcemicroscopy (AFM) was used to characterize the morphology of thefilms. Un-doped V2O5 and doped with 3% concentration of Nd andCe films have direct allowed transition band gap. The mechanisms ofdc-conductivity of un-doped V2O5 and doped with Nd and Ce filmsat the range 303 K to 473 K have been discussed.